STRATEGI PENGEMBANGAN KOMPETENSI GURU PAUD MELALUI KOMUNITAS BELAJAR - Abdullah Zaky; Siti Aisyah; Kokom Komariah; Mutoharoh; Siti Khoeriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of competencies among Early Childhood Education (ECE/PAUD) teachers has become a strategic necessity to ensure contextual and sustainable learning quality. One increasingly applied approach is the strengthening of learning communities collaborative spaces in which teachers share practices, engage in joint reflection, and design follow-up actions based on field needs. An effective learning-community model integrates peer learning (practice sharing), mentoring/coaching, small-scale classroom action research, and the use of digital platforms for documentation and learning resources. Empirical findings show that teacher engagement within learning communities has a significant impact on improving pedagogical competencies as well as the ability to design and implement instruction. Recommended practical strategies include:(1) routine meetings centered on real instructional problems (problem-centered meetings) so that discussions directly lead to teaching solutions,(2) peer observation and structured feedback to accelerate the transfer of effective practices,(3) focused mentoring by facilitators/mentors during the design and implementation phases of learning outcomes (including literacy/STEAM content in early childhood education),(4) the use of digital platforms (e.g., the Merdeka Mengajar Platform) to archive lesson plans, assessment rubrics, and shared modules, thereby improving crosslocation collaboration; and (5) continuous evaluation mechanisms (reflection, monitoring, and follow-up actions) to ensure that changes in practice are sustainable. These strategies have been implemented in mentoring programs and proceedings that incorporate digital platforms to support the implementation of the Merdeka Curriculum. Research and community-service studies demonstrating the effectiveness of learning communities in ECE contexts often use quantitative designs (to test the influence of community participation on teacher competence) and PKM/implementation approaches (to design mentoring interventions and evaluate their outcomes). These findings consistently indicate an increase in teachers’ pedagogical abilities after